ANALYSIS OF SHOT CONCRETE MATERIAL MIXTURE ON UNDERGROUND MINE BUFFER: ANALISIS CAMPURAN MATERIAL BETON TEMBAK PADA PENYANGGA TAMBANG BAWAH TANAH - BODIAN DAVIN PANGGABEAN BODIAN (INTAN Jurnal Penelitian Tambang, 2024)
To increase the stability of the opening hole, it is done by increasing the strength of the rock around the opening hole through support. The buffering method used at PT Antam underground is shotcrete. Shotcrete is a cement mixture that is passed through spraying equipment and shot at high speed on the surface of the walls and roof of the tunnel. The research was conducted in the underground area, panel 20. The problem in panel 20 is testing the mixing results that do not reach the target. To answer this problem, tests were carried out on the quality of shotcrete material which included testing the aggregate grain size, moisture content, and mud content. From the results of testing the quality of the material, it was found that there were still coarse aggregates that did not meet the standard requirements of ASTM D-1140 grain arrangement, moisture content in sand ranged from about 2.6% to 6.3%, moisture content in sample VIII was still high, reaching 20.1%, mud content reached 12.3% and 17.5% greater than the percentage value of normal mud content of 5%. The existence of testing the physical properties of this shotcrete mix material to control the quality of the targeted shotcrete and later not harm when it is applied in the field.